Education and care for adolescents and adults with autism - Wall, Kate (SAGE Publications, 2007)
By providing case studies and examples that show the reader how to put theory into practice in multi-disciplinary settings, this book clearly explains how changes in policy and provision have affected the ways in which young people and adults with autism are cared for and educated. This book offers up-to-date, accessible information on: o the nature and effects of Autistic Spectrum Disorders (ASDs). o family issues surrounding caring for and educating those with ASDs. o possible intervention programmes. o how to support the family. Based on years of experience gained in education and care sett.